2015
DOI: 10.1039/c4ra13547d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cancer and the anticancer activities of naphthoquinones – a review

Abstract: The non-communicable disease, cancer, is one of the major causes of death across the world and is forecast to increase by 75% to reach close to 25 million cases over the next two decades. Radiotherapy and surgical approaches have been unsuccessful in controlling the incidence of most cancers. The development of chemotherapeutic strategies involving novel small molecule antitumour agents has therefore been the focus area of cancer chemotherapy for several decades as another strategy to combat and control the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
221
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(232 citation statements)
references
References 255 publications
(266 reference statements)
4
221
1
6
Order By: Relevance
“…Their derivatives have exhibited a variety of biological responses which include antiallergic, antibacterial, antifungal, anti-inflammatory, antithrombotic, antiplatelet, antiviral, apoptosis, lipoxygenase, radical scavenging, and anti-ringworm activities. Many studies have shown that naphthoquinones have biological activities specifically against pathogenic protozoa and cancer cells owing to their privileged structures in medicinal chemistry [17]. In this study, we obtained a series of naphthoquinone aglycones and glucosides, and then presented the isolation and structural elucidation of four new naphthalenyl glucosides (compounds 18, 25-27), together with 23 known compounds from green walnut husks of J. mandshurica Maxim.…”
Section: Introductionmentioning
confidence: 99%
“…Their derivatives have exhibited a variety of biological responses which include antiallergic, antibacterial, antifungal, anti-inflammatory, antithrombotic, antiplatelet, antiviral, apoptosis, lipoxygenase, radical scavenging, and anti-ringworm activities. Many studies have shown that naphthoquinones have biological activities specifically against pathogenic protozoa and cancer cells owing to their privileged structures in medicinal chemistry [17]. In this study, we obtained a series of naphthoquinone aglycones and glucosides, and then presented the isolation and structural elucidation of four new naphthalenyl glucosides (compounds 18, 25-27), together with 23 known compounds from green walnut husks of J. mandshurica Maxim.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxynaphthoquinones are pharmacologically important molecules they possess several biological activities which includes, anticancer [5] and antibiotic [6] etc. Hydroxynaphthoquinones exist in tautomeric equillibria in solutions contrary to only one stable tautomeric form in solid [7].…”
Section: Introductionmentioning
confidence: 99%
“…80,81 An important variation, the water-soluble prodrug ARQ 761 which does not have a structure published to date, currently has two ongoing Phase I clinical trials that are recruiting for patients with solid cancers in one trial, and in conjunction with gemcitabine, directed against pancreatic cancer in the other. ARQ 761 is listed as being β-lapachone in a recent review by Wellington 82 where he is discussing the anticancer activities of naphthoquinones. However, Arqule reports that it is a prodrug of β-lapachone.…”
Section: Lapachol and Lapachonementioning
confidence: 99%